ISOLATION AND SELECTION OF ALKALINE PROTEOLYTIC BACTERIA FROM LEATHER PROCESSING WASTE AND ENZYME CHARACTERIZATION - BUDIASIH WAHYUNTARI; NISA R MUBARIK; MARITA ANGGARANi (BIOTROPIA, 2004)
ABSTRACT The aims of this experiment were to isolate alkaline protease producing bacteria from leather processing waste, and to study the biochemical properties of the enzyme produced by the selected bacteria. Nine bacterial isolates incubated at 37"C, revealed proteolytic activity on skim milk containing media. Four isolates were grown at pH 9 and another four isolates at pH 10 and only one isolate at pH 11. However, in further subculture, there were only three isolates that showed proteolytic activity, namely, D2, D7, and Dl l .Â  Among the three isolates, isolate D2 was the highest protease producer. The highest protease production (36.5U/L) was reached after a 36-hr fermentation at pH 9. The optimum activity of D2 protease was observed at pH 8 and 60"C. The enzyme was stable at pH range of 7-10, and at temperature of 52-62"C. In the presence of 5mM EDTA or PMSF, the crude enzyme activity decreased to 7.04% and 23.29% respectively, which indicated that the enzyme might be a metal dependent serine protease. Zymogram analysis revealed the molecular weight of the enzyme was about 42.8kD. Keywords:Â  leather/ waste/protease/alkaline